Say No To Bulliying: Pencegahan Bulliying di Tingkat Sekolah Dasar - Nandy Agustin Syakarofath; Devina Andriany; Rizkita Audira Fernanda; Mariska Balqis Zharifah; Amarillys Erina Rahadi; Devinta Yurika Fitria; Nurgita Fitria Sari (Jurnal Kabar Masyarakat, 2026)
Bullying is a global and national issue that requires special attention and effective preventive measures, particularly in elementary school environments. This community service program aimed to prevent bullying through a psychoeducational pilot study conducted at a model elementary school in Malang City. The activity actively involved approximately 28 students through a series of educational and interactive methods, namely the psychoeducational sessions Say No to Bullying for Kids and Developing Empathy in Kids, the screening of a cartoon film on bullying prevention, and a self-awareness activity conducted through a Focus Group Discussion (FGD). Based on the program evaluation, the students stated that the entire series of activities was enjoyable, engaging, and easy to understand. The activities successfully enhanced students’ understanding of the importance of preventing aggressive and harmful behaviors, including bullying, while fostering awareness that such behaviors should not be practiced. Through the implementation of this pilot study, it is expected that children’s social-emotional awareness will continue to develop positively, thereby helping to reduce or minimize the potential occurrence of bullying cases, at least within the school environment that served as the community service partner.